Acute Effects of Insulin on Cardiac Function in Patients with Diabetes Mellitus: Clinical Applicability and Feasibility. (17th March 2020) - Daoud Naccache, Deeb; Yalonetsky, Sergey; Bar-Yoseph, Ronen
Abstract : Background . Insulin promotes glucose consumption as the main cardiac energy source, while increasing myocardial efficiency. The short-term effects of insulin on cardiac function and its potential curative role in an acute diabetological cardiology setting remain unknown. Our study evaluated the role of acute insulin administration in the diabetic heart, its corresponding effective blood insulin level, and the time-course applicability of insulin treatment in a routine clinical setting. Methods . We evaluated a case series of six male (48.1 ± 4.9 y/o) patients with controlled diabetes (HbA1c of 6.6 ± 0.3%) and disease duration of 14.4 ± 6.7 yr. Each subject was evaluated for glucose homeostasis, as well as hemodynamic and echocardiographic (systolic and diastolic) parameters at three points: baseline followed by two successive insulin loads in euglycemic hyperinsulinemic clamp study. Results were analysed using Student's t -test. Results . The first insulin load led to a physiologic blood insulin level of 145 ± 36  μ U/ml, and both systolic (7 mmHg) blood pressure and diastolic (4 mmHg) blood pressure decreased significantly. Left ventricular fractional shortening (LVFS) increased significantly by 11.8%. Diastolic function parameters of mitral annulus movement of the A′ wave increased relative to baseline by 20.0% (27.8% under the second insulin load), A′ medial increased relative to baseline by 30%, and A′ lateral increased relative to baseline by 17%, displayed by tissue Doppler imaging. Conclusions . Insulin acutely affected the diabetic heart at a physiologic level within a 2 h time course. Insulin mainly increased left ventricular systolic function and, to a second degree, improved left ventricular diastolic functions and atrial systole in diabetic subjects. These results may facilitate the development of insulin-based acute treatment in diabetic patients with cardiac morbidity. This trial is registered with NCT02962921 .